Phản ứng aldol chọn lọc lập thể. Phần 1: Các phát triển gần đây và ứng dụng trong tổng hợp hữu cơ. - Thuận, Ngô Thị; Hiển, Nguyễn; Tuấn, Đặng Thanh (Vietnam Journal of Chemistry, 2017)
The Aldol reaction is one of the most important C–C bond forming tools. Recent developments of chiral catalyst systems allowed the Aldol reaction to be carried out under mild conditions, affording products in high yields as well as high diastereo- and enantioselectivities with very good tolerance of functional groups. This review offers an overview of some important concepts in the stereoselectivity of the Aldol reaction and then highlights the recent developments of new chiral catalyst systems (focused on metal catalysts) which yielded the Aldol addition products in the excellent control of diastero- and enantioselectivities. In addition, several practical applications of the Aldol reaction in the total synthesis of complex molecules, such as bioactive natural products and pharmaceuticals, are demonstrated in this review. Keywords. Aldol reaction, Mukaiyama-Aldol reaction, asymmetric Aldol reaction, stereoselectivity, enantioselectivity, enolate chemistry.